CEO Characteristics and Earnings Management - RAHMAT DWI SANTOSO; FUAD RAKHMAN (The Indonesian Journal of Accounting Research, 2013)
This study investigates the relationship between the characteristicsof CEOs and earnings management among public firms listedon the Indonesian Stock Exchange. The decision on how to manageearnings is in the hands of corporate executives. This study examines ifearnings management is affected by the characteristics of companyCEOs. Using 265 firms in 2012 as our sample, we find that the shortertenure, older, and founding family CEOs report lower absolute discretionaryaccruals. Further, we did not find any association between theCEOs’ gender and earnings management.